Influence of gas dissociation and xenon addition on steady-state microwave-excited c02 laser discharges - Grudszus, S.; März, Martin (Journal of Physics D: Applied Physics, 1993)
The electron energy distribution in a microwave-excited mixture of He, N2, C02, Xe, CO and 02 was calculated by numerically solving the Boltzmann equation, using collision cross section data for 69 elastic and inelastic collision processes. At an excitation frequency of 2.45 GHz the energy distribution is quasi-stationary for gas pressures up to about 100 mbar. By balancing the most important processes of electron generation and loss, the reduced field E/N and the electron density nB in a seif-sustained steady-state discharge were calculated for various gas mixtures and excitation parameters. Curves are presented showing that with increasing C02 dissociation, the stationary value of E/N within the plasma rises, combined with drastically reduced rates for vibrational excitation of C02 (00*1) and N2. In contrast the admixture of xenon reduces the steady-state E/N value and thus the mean electron energy, leading to an increased electron density and excitation efficiency. These effects are in good agreement with experimental observations. © 1993 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up